Unrealistic optimism and HEXACO traits as predictors of risk perception and compliance with COVID-19 preventive measures during the first wave of pandemic - Milan Oljača; Selka Sadiković; Bojan Branovački; Dejan Pajić; Snežana Smederevac; Dušanka Mitrović (Primenjena Psihologija)
The aims of this study were to examine possible differences and factors that contribute to risk perception and compliance with preventive measures at the beginning (T1) and the end (T2) of the first wave of COVID-19 pandemic. The sample consisted of 423 participants (M = 30.29, SD = 14.45; 69% female). Compliance, risk perception and trust in information were significantly higher in T1 than T2. For risk perception, significant predictors in both T1 and T2 were age, Emotionality (HEXACO-PI-R) and Unrealistic Optimism (NLE, Negative Life Events). Trust in information was a significant predictor in T1, while Unrealistic Optimism (Positive Life Events) was a significant predictor in T2. For compliance, significant predictors in T1 were gender and trust in information while in T2 were Emotionality, Extraversion, Conscientiousness (HEXACO-PI-R), NLE and trust in information, for both T1 and T2. In general, findings suggest a much more pronounced role of personality traits in adherence to protective measures at the end than at the beginning of the first wave of the COVID-19 pandemic in Serbia. Also, the results indicate the role of unrealistic optimism regarding negative life events in lower compliance with protective measures.